MEASURING ENVIRONMENTAL COSTS AND QUALITY COSTS AND THEIR ROLE IN IMPROVING PRODUCT QUALITY AND ACHIEVING CUSTOMER SATISFACTION - Fatemeh Darogheh Hazrati; Saud Jabbar Muhammad; Saadoun Jabbar Muhammad; Mustafa Habib Naima; Mustafa Taleb Najma (Scholar Express Journals, 2022)
The research dealt with the objective of environmental costs and quality costs, and through this study, the concept of environmental costs, its objectives and types in terms of its association with the economic institution and in terms of its financial effects on the economic unit, was identified. Disclosure is a presentation of information related to environmental activities, and the importance of disclosing environmental costs was mentioned, as it was found that it is the factor that gives legitimacy to the activities carried out by various economic institutions, and environmental disclosure increases the community's confidence in establishments that fulfill their environmental responsibilities. There are several problems and difficulties encountering the process of measuring environmental costs, which must be overcome or facilitated. As for the methods of measuring environmental costs, there were many, including those that depend for their measurement on traditional markets of various types, and others that depend on virtual markets. With regard to quality costs, its multiple concepts and dimensions have been identified, as quality is the suitability of the product for use, and quality costs are the costs incurred to prevent the production of a low-quality product, and quality costs are important to the reputation of the institution, and have a role in consumer protection, the application of the quality system It leads to a significant increase in the market share of productive institutions, as well as an increase in productivity and quality costs. The higher the quality , the higher the productivity and the lower costs. Quality costs are on two types of conformity (prevention and evaluation), and non-conformity (internal failure and external failure), as it was found that the higher the conformity costs, the lower the non-conformity costs, and it was recommended to increase the investment in prevention costs to the level at which its positive impact remains in reducing Quality costs in general and the costs of internal failure and external failure in particular, and that attention should be paid to quality costs as they affect the quality of the product provided to the consumer, and prevention costs occupy the highest relative importance among the types of costs because they contribute effectively to reducing the occurrence of other costs of quality The methods of analyzing quality costs are also numerous, the most important of which are trend analysis and Pareto analysis, where the latter is considered one of the most successful techniques in analyzing quality costs and one of the most powerful tools that man has invented.
Keywords: Environmental costs; quality costs; types of environmental costs; types of quality costs